Synthesis and characterization of organotin(IV) thiobiurets - Rastogi R.B.; Singh K.; Maurya J.L. (My University, 2025)
Some triphenyltin and dibutyltin thiobiurets of the type Ph 3SnL and Bu 2SnL 2/ [where LH = 1,5 diphenyl-2-thiobiuret (PPTBH), 1-(4-ethoxyphenyl)-5-phenyl-2-thiobiuret (EtOPPTBH), or 1-naphthyl-5-phenyl-2-thiobiuret (naphPTBH)], have been synthesized and characterized by elemental analysis and various physicochemical techniques. Molar conductance measurements show the non-ionic behavior of the complexes. FAB mass spectra exhibit their monomeric nature. 1H and 13CNMR spectra support the proposed stoichiometry of the complexes. Infrared spectra suggest monoanionic bidentate mode of bonding of the ligands. The powder XRD patterns of the complex Bu 2Sn (PPTB) 2are indicative of triclinic crystal system. Copyright © Taylor & Francis Group, LLC.